Focoxanthin extractions of brown seaweeds and analysis of their tipid fraction in methanol - Jaswir, Irwandi; Noviendri, Dedi; Mohd. Salleh, Hamzah; Miyashita, Kazuo (Japanese Society for Food Science and Technology, 2012)
In this present study, fucoxanthin has been successfully extracted and purified from two species of Malaysian brown seaweeds, namely Sargassum binderi and S. duplicatum. The purity of the fucoxanthin obtained was > 99% as indicated by HPLC analysis. Both fucoxanthincontent, and analysis of lipid fraction of the seaweeds in methanol showed that both samples contained a considerable amount of fucoxanthin and total lipids. The amount of fucoxanthin and total lipid farcation in methanol of S. duplicatum (1.01 ± 0.10 and 21.3 ± 0.10 mg/g dry-weight, respectively) was significantly higher than those of S. binderi (0.73 ± 0.39 and 16.6 ± 4.10, respectively). Both types of seaweeds also contained a considerable amount of unsaturated fatty acids. However, in terms of docosahexanoic acid, eicosapentanoic acid, arachidonic acid, linoleic acid and alpha-linolenic acid contents, S. duplicatum was found to be higher (0.76, 2.55, 13.64, 5.81 and 5.35 %, respectively) than S. binderi (0.70, 1.82, 9.13, 6.37 and 4.39%, respectively). For saturated fatty acids, palmitic (C16:0) was found to be the major fatty acid in both samples studied.